Real urban images: Policy and culture in northern Britain - Wharton, Chris; Fenwick, John (Culture and Local Governance / Culture et gouvernance locale, 2012)
This paper explores recent attempts to re-imagine and re-brand northern British cities through processes of economic and (mainly) cultural regeneration. It analyses the creation of new contemporary urban images and presentations and compares these with the economic, social and cultural life experiences of people living in the areas. It examines the process of recharacterising former industrial conurbations as being at the cutting edge of contemporary, postmodern culture. A range of features is identified here within similar political, economic and policy contexts: deindustrialisation and regeneration driven by local business and political elites; emphasis on culture as spectacle to the exclusion of other cultural configurations; reliance on tourism and advertising, hyper consumption and leisure as determining aspects of the local economy; and the reorganisation of city populations.